2022
DOI: 10.1136/jitc-2022-005651
|View full text |Cite
|
Sign up to set email alerts
|

T cells of colorectal cancer patients’ stimulated by neoantigenic and cryptic peptides better recognize autologous tumor cells

Abstract: BackgroundPatients with cancers that exhibit extraordinarily high somatic mutation numbers are ideal candidates for immunotherapy and enable identifying tumor-specific peptides through stimulation of tumor-reactive T cells (Tc).MethodsColorectal cancers (CRC) HROC113 and HROC285 were selected based on high TMB, microsatellite instability and HLA class I expression. Their HLA ligandome was characterized using mass spectrometry, compared with the HLA ligand atlas and HLA class I-binding affinity was predicted. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Second, there is no guarantee that neoantigens identified in silico will be expressed unmodified at the protein level and presented by tumor cells in their native state. Further, reliance on exomic mutational profiling omits immunogenic neoantigens derived from other tumor metabolic derangements, such as altered RNA editing, proteomic processing, or non-canonical translation [37] , [38] , [39] . This is supported by studies demonstrating TCR recognition of patient-derived xenograft tissue in the absence of reactivity against predicted peptide neoantigens [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is no guarantee that neoantigens identified in silico will be expressed unmodified at the protein level and presented by tumor cells in their native state. Further, reliance on exomic mutational profiling omits immunogenic neoantigens derived from other tumor metabolic derangements, such as altered RNA editing, proteomic processing, or non-canonical translation [37] , [38] , [39] . This is supported by studies demonstrating TCR recognition of patient-derived xenograft tissue in the absence of reactivity against predicted peptide neoantigens [32] .…”
Section: Discussionmentioning
confidence: 99%
“…When comparing gene expression of proteins involved in antigen processing 14 between our two tumor models and normal colon tissue, the majority of genes showed a higher expression in tumor than in normal tissue; hinting at a preservation of functional antigen processing. Even though B2M expression was decreased, a HLA ligandome analysis revealed thousands of HLA-eluted peptides in both cell lines 20 . Thus, the presentation of tumor-specific peptides with the potential to activate T cells was maintained in these two CRC cases, contrasting the well-established correlation of MSI and diminished HLA expression 2224 .…”
Section: Discussionmentioning
confidence: 99%
“…In both tumor cell lines, the mean expression of the selected genes resembled or even exceeded the levels in CRC samples from TCGA, but due to the small size of the cell line cohort (n=2), statistical analysis was inadmissible. Moreover, functional antigen processing was previously assured through HLA ligandome analyses enabling the characterization of several thousand HLA ligands for each CRC cell line, including tumor-specific antigens 20 .…”
Section: Hroc113 and Hroc285 T0 M2 Express Genes Of The Antigen-proce...mentioning
confidence: 99%
“…Moreover, following tetramer staining, it was revealed that most TILs and peripheral blood T cells were specific for IQGAP1 neoantigen. [98] Regarding the low tumor mutational burden in some tumors, the abundance of neoantigens in them is limited. An alternative chemical-based compound (RECTAS) to generate spliceneoantigens in CRC mice models.…”
Section: Nrt Immunotherapy In Colorectal Cancermentioning
confidence: 99%
“…Moreover, following tetramer staining, it was revealed that most TILs and peripheral blood T cells were specific for IQGAP1 neoantigen. [ 98 ]…”
Section: Nrt Immunotherapy In Colorectal Cancermentioning
confidence: 99%